Legal Regulations of Healthcare Right ın Georgia - Mgeladze, Nazi (European Scientific Journal, ESJ, 2017)
The right to health care is one of the fundamental human rights recognized and protected by the Constitution of Georgia, as well as the international treaties and other national legislative instruments. The right to health care has the meaning of social right and is enshrined in the Article 37 of the Constitution of Georgia. The above-mentioned article is one of the articles with a wide scope and content, covering two most important areas of public life: health care and natural environment. On the one hand, it obliges the State to provide access to medical services and environment protection, and, on the other hand, entitles an individual to benefit from medical insurance and aid, to live in a healthy environment, to obtain full and objective information as to the state of environment, as well as obliges everyone to care for the natural and cultural environment. This right / obligation shall apply to the citizens of Georgia, as well as to foreign citizens and stateless persons. Provision of the right to health care is depended upon the activity of the State, in particular, implementation of the obligations stipulated by the state medical programs in the health care sector, which should be provided by the country’s health care system.